Can the Road and Belt Project Be an Alternative Solution to Established Global Flow Routes? (Economic and Political Thought, 2023)
This study aims to answer the question contained in its title: Can the Roadand Belt project be an alternative to the current global flow routes? Thelogical axis of the article is the role of the logistics system in the competitivenessof countries and the effectiveness of projects such as BRI. The articleis a literature review.The article contains an introduction that discusses the history of the BRIinitiative and its main conditions. The first chapter presents the conceptof the country’s logistics system and its impact on the country’s economiccompetitiveness. The second chapter discusses the development of China’slogistics system, which is the initial phase initiating the BRI project. Chapterthree discusses China’s investments in BRI member countries, with particularemphasis on transport and logistics projects. The article ends with finalconclusions.
Keywords: logistics, Belt and Road Initiative, products flows